1999
DOI: 10.1046/j.1365-2761.1999.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine development for winter ulcer disease, Vibrio viscosus, in Atlantic salmon, Salmo salar L.

Abstract: Coldwater Vibrio species isolated from Atlantic salmon, Salmo salar L., during winter ulcer disease outbreaks at saltwater sites in Norway and Iceland were characterized phenotypically, tested for virulence, and used to evaluate the efficacy of multivalent, oil‐adjuvanted vaccines. The intraperitoneal (i.p.) injection of rainbow trout, Oncorhynchus mykiss (Walbaum), in fresh water with one bacteria species isolated during winter ulcer outbreaks, V. ‘viscosus’, produced rapid mortality and disease signs which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…Isolates from Atlantic salmon in Norway must therefore account for the overwhelming majority of clinical M. viscosa isolates on a worldwide basis. Despite the antigenic differences identified during the present study and by Heidarsdóttir et al (2008), crossprotection has been reported between Icelandic (presumed variant) and Norwegian (typical) strains (Greger & Goodrich 1999). The previous assumption of homogeneity may therefore not have been as significant in relation to protection of vaccinated stocks as it otherwise might have been.…”
Section: Discussioncontrasting
confidence: 66%
“…Isolates from Atlantic salmon in Norway must therefore account for the overwhelming majority of clinical M. viscosa isolates on a worldwide basis. Despite the antigenic differences identified during the present study and by Heidarsdóttir et al (2008), crossprotection has been reported between Icelandic (presumed variant) and Norwegian (typical) strains (Greger & Goodrich 1999). The previous assumption of homogeneity may therefore not have been as significant in relation to protection of vaccinated stocks as it otherwise might have been.…”
Section: Discussioncontrasting
confidence: 66%
“…2003). However, cross protection between an Icelandic and a Norwegian strain has been reported (Greger and Goodrich 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several challenge models have been established for experimental infections in fish by a range of bacteria and viruses with exposure methods including direct injection of the pathogen (e.g. Nordmo & Ramstad 1997; Greger & Goodrich 1999; Aranguren, Tafalla, Novoa & Figueras 2002; Bowden, Smail & Ellis 2002; Thoulouze, Bouguyon, Carpentier & Bremont 2004; Björnsdóttir, Gudmundsdóttir, Bambir & Gudmundsdóttir 2005; Byon, Ohira, Hirono & Aoki 2005; Caipang, Takano, Hirono & Aoki 2006), cohabitation of naïve fish with infected individuals (e.g. Nordmo & Ramstad 1997; Jones & Groman 2001; López‐Dóriga, Smail, Smith, Doménech, Castric, Smith & Ellis 2001; Bowden et al 2002; Klesius, Evans, Shoemaker & Pasnik 2006) and water‐borne exposure (e.g.…”
Section: Introductionmentioning
confidence: 99%